Belize. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Belize during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as apiculture, sustainability, cooperation between the public and private sectors, health and food safety, agrotourism, bioeconomy, resilience against climate change, biosecurity in the management of chicken coops and control of pests that affect birds. Likewise, work was done on antimicrobial resistance, on improving the banana production chain, on drainage systems and on soil fertility. Finally, contributions were made in financing, in training, and in optimizing the data system for farmers and georeferenced data, systems that have not yet managed to include small and medium-sized enterprises.